Urban computing - Zheng, Yu (Data scientist) (Information systems, 2018)
Although there are a few books on urban informatics, this is the first book dedicated to urban computing, with a broad spectrum of coverage and an authoritative overview. This book introduces a general framework, key research problems, methodologies and applications of urban computing from a computer science perspective. More specifically, this book focuses on data and computing, distinguishing urban computing from tradition urban science based on classical models and empirical assumptions. Rapid urbanization has led to the expansion of numerous large cities, not only modernizing many people's lives but also posing big challenges, such as air pollution, energy consumption and traffic congestion. Tackling these challenges seemed nearly impossible only a few years ago given the complex and dynamic settings of cities. Nowadays, sensing technologies and large-scale computing infrastructure have produced a variety of big data, such as human mobility, meteorology, traffic patterns and geographical data. The corresponding big data implies rich knowledge about a city and can help tackle these challenges when used correctly. In addition, the rise of computing technology, such as cloud computing and artificial intelligence (AI), has provided us with unprecedented data processing capabilities...